The Surgical Treatment of Severe Endometriosis Positively Affects the Chance of Natural or Assisted Pregnancy Postoperatively. (12th July 2015) - Nesbitt-Hawes, Erin M.; Campbell, Neil; Maley, Peta E.; Won, Haryun; Hooshmand, Dona; Henry, Amanda; Ledger, William; Abbott, Jason A.
Abstract : Objective. To report reproductive outcomes following laparoscopic surgical excision of histologically confirmed r-ASRM stage III-IV endometriosis. Study Design. A retrospective cohort study was performed at the Royal Hospital for Women, a university teaching hospital, Sydney, Australia. Women who had fertility-preserving laparoscopic excision of stage III-IV endometriosis from 1997 to 2009 were contacted regarding reproductive outcomes. Results. In the study period, 355 women underwent surgery for stage III-IV endometriosis. Follow-up data are available for 253/355 (71%) women. Postoperatively, 142/253 (56%) women attempted to conceive with a conception rate of 104/142 (73%). Confidence intervals for pregnancy for women who were attempting conception (including the nonresponders) range from 104/262 (40%) to 224/262 (85%). Median time to conception was 12 months. No positive prognostic factors for pregnancy were identified on regression analyses. Conclusions. These data provide information to women with suspected severe disease preoperatively concerning their likely postoperative fertility outcomes. Ours is a population with severe endometriosis, rather than an infertile population with endometriosis, so caution needs to be applied when applying these data to women with fertility issues alone.